2022
DOI: 10.1039/d1fo03847h
|View full text |Cite
|
Sign up to set email alerts
|

A Lupinus angustifolius protein hydrolysate exerts hypocholesterolemic effects in Western diet-fed ApoE−/− mice through the modulation of LDLR and PCSK9 pathways

Abstract: Lupin protein hydrolysate (LPH) is gaining attention in the food and nutraceutical industries due to several beneficial health effects. Recently, we have shown that LPH treatment reduces liver cholesterol and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 65 publications
(104 reference statements)
0
21
0
Order By: Relevance
“…The latter was lyophilized and stored at 20−25 °C. 20 Concentration of proteins, 20 total dietary fiber, 25 oil content, 26 soluble sugars, 27 polyphenols, 28 degree of hydrolysis, 29 molecular weights profile, 20 and peptides identification 22 were measured as previously described (see the Supporting Information for more detail).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter was lyophilized and stored at 20−25 °C. 20 Concentration of proteins, 20 total dietary fiber, 25 oil content, 26 soluble sugars, 27 polyphenols, 28 degree of hydrolysis, 29 molecular weights profile, 20 and peptides identification 22 were measured as previously described (see the Supporting Information for more detail).…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…21 Furthermore, the molecular analysis of the in vivo LPH effects on the cholesterol metabolic pathway of liver showed that LPH regulates the activation of HMGCoAR, the main enzyme responsible for cholesterol synthesis, and the protein levels of LDL-C receptor (LDL-R). 22 In addition, we have reported the beneficial effects of a functional beverage based on LPH on the antioxidant and anti- inflammatory status as well as decreasing of the atherogenic index in healthy subjects. 23 In light of these considerations and because no previous studies have addressed the pleiotropic actions of bioactive peptides from lupin in the key components of the early stages of atherosclerosis (hyperlipidemia, oxidative stress, and inflammation), the main objective of this study was to analyze the effects of LPH on early risk factors for atherosclerosis in a WD-induced hypercholesterolemia model in ApoE −/− mice.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Moreover, recent studies have shown a strong link between high cholesterol levels and anxiety [ 69 ]. Our group has previously shown that LPH exerts anti-inflammatory, antioxidant, and lipid-lowering effects both in ApoE −/− mice [ 47 , 73 ] and humans [ 45 , 46 ]. Therefore, we suggest that these LPH properties may also be directly or indirectly responsible for the anxiolytic-like effects.…”
Section: Discussionmentioning
confidence: 99%
“…The peptide spectra were obtained using the same parameters described in our previous work [ 73 ]. The protein sequence database of L. angustifolius (31,386 sequences) was downloaded from UnitProt and used for the identification of raw data spectra using Proteome Discoverer v1.3 (Thermo) in combination with the Mascot search engine v2.3.02.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation